Sexual harassment: why men do it? A study to examine the predictors that leads men to sexually harass - Kenny, Kamal; Abu Samah, Asnarulkhadi; Othman, Jamilah (Center for Promoting Ideas, 2011)
Sexual harassment is a phenomenon that has always been looked from a woman’s perspective. Almost all earlier studies on sexual harassment look at the incidences of sexual harassment, the effects on victims and coping strategies for victims. There is a dire need to change our understanding of this issue. In order to obtain a more holistic view of this issue, there should be a paradigm shift where the focus should be on the perpetrators. As men are generally the perpetrators, it is hoped that an insight into background, thoughts, feelings, perceptions and attitude would help understand why this phenomenon does exist. A total of 900 male respondents were interviewed using a structured questionnaire. The major finding of the study shows that men, regardless of his position and status, view sexual harassment as a sexual act, rather than a crime that affects the victims in many ways. Therefore, men are generally ignorant to the fact that their behaviour are subject to legal action.